Sustainable Bioplastics Made from Cassava Peel Waste Starch and Carrageenan Formulations: Synthesis and Characterization - Fadhallah, Esa Ghanim; Assa'diyah, Indah Nurul; Juwita, Nana; Tullaila, Sholeha; Yudistiro, Muhammad Kahfi Kharisma; Zuidar, Ahmad Sapta; Dameswary, Amarilia Harsanti (Universitas Jenderal Soedirman, 2024)
Plastic waste has become a global environmental problem as it is difficult to decompose and harms the environment. The alternative solution to overcome this problem is to produce biodegradable plastics made from renewable materials. Cassava peel waste contains starch that can form a thin film but has poor mechanical properties. Therefore, it is necessary to include additional substances to enhance its strength. Carrageenan is a substance that can improve bioplastic mechanical properties. This study aims to determine the characteristics of bioplastic made from cassava peel waste starch and carrageenan formulation. Nine formulations were tested in this study using the randomized complete block design factorial with the two factors of cassava peel starch (S) and carrageenan (C) concentrations, both at three levels and carried out under three replications. Bioplastics characteristics are observed in thickness, swelling, biodegradation, tensile strength, elongation, and elasticity. The formulation S2C1 (starch 20%; carrageenan 5%) produced the bioplastic with the best mechanical properties, including a tensile strength of 1.1 MPa, elongation of 1.33%, and elasticity of 0.87. Meanwhile, the formulation S3C1 (starch 30%; carrageenan 5%) had the best results for swelling, thickness, and biodegradability, with a swelling value of 57.79%, thickness of 0.36mm, and 11-day biodegradability.